A Comparative Study on Flexural Capacity of Reinforced Concrete Beams Reinforced with GFRP and Steel Bars - Muhammad Rafani; Tavio; Francisco Jose De Caso y Basalo (Advances in Technology Innovation, 2026)
This study compares the flexural capacity of reinforced concrete (RC) beams reinforced with glass fiber-reinforced polymer (GFRP) bars and conventional steel bars. It examines how reinforcement ratio affects relative moment-capacity performance. Twelve beam specimens are tested under four-point bending with reinforcement ratios from 0.5% to 2.4%. All specimens have identical geometry, transverse reinforcement, and loading configuration. Experimental moment capacities are calculated from ultimate loads and compared with Canadian Standards Association (CSA) S806-12-based predictions for GFRP-reinforced beams. At low reinforcement ratios (ρ ≤ 1.0%), GFRP-reinforced beams develop moment capacities comparable to or higher than steel-reinforced beams because of the high tensile strength of GFRP. At higher reinforcement ratios, steel-reinforced beams achieve larger capacities due to yielding and stress redistribution. The results indicate a gradual transition zone around ρ ≈1.1-1.2%, rather than a strict threshold. CSA predictions are generally conservative, except for the lowest-ratio GFRP specimen. These findings support comparative design.